Mechanisms for Preparing Future Teachers to Design An Educational Environment in The Conditions of Digitalisation - Kryvylova , Olena; Prima , Raisa; Fizeshi , Oktaviia; Oleksenko , Karina; Kurylo , Olha; Oleksenko , Roman; Kotelianets , Natalka; Chernysh , Natalia; Khrystova , Tеtіana; Pyurko , Vladyslav (International Journal of Basic and Applied Sciences, 2025)
Mechanisms for preparing future teachers to design an educational environment in the context of digitalization include the development of digital competence, mastering digital educational system design technologies, training in interaction with digital tools, and training in creating educational content. The article analyzes the operational-activity component of future primary school teachers’ readiness to design the educational environment. The focus is placed on the development of practical skills, the ability to organize the educational process considering the variability of primary education, and the effective use of available resources. Mastery of this component is seen as a key factor in creating a safe, functional, and adaptive learning space that meets the demands of modern primary education. An important role in this process is played by information technologies, which influence psychological mechanisms (cognitive processes, metacognitive skills, emotional and volitional qualities, and reflexivity). The pedagogical research implemented a set of organizational and pedagogical conditions aimed at enhancing this component: fostering positive motivation for project-based activities; updating the practice-oriented content of professional training disciplines; introducing forms and methods of instruction focused on practical modeling of the educational environment; and engaging students in reflective activities throughout the preparation process. The experimental results demonstrated a positive dynamic in the development of the operational-activity component, in particular, an increase in initiative, creativity, and the ability to independently solve multilevel tasks. The reliability of the observed changes was confirmed using statistical methods, including Student’s T-test and Pearson’s chi-square test. The findings affirm the effectiveness of the proposed conditions in preparing a competent teacher for the New Ukrainian School who can design a child-centered educational environment.
Keywords: Professional Activity; Psychological Mechanisms; Information Technologies; Digitalisation; Education